Characterising vent and crater shape changes at Stromboli: implications for risk areas - Schmid, Markus; Kueppers, Ulrich; Civico, Riccardo; Ricci, Tullio; Taddeucci, Jacopo; Dingwell, Donald B. (Volcanica, 2021)
Active volcanoes are typically subject to frequent substantial topographic changes as well as variable eruption intensity, style and/or directionality. Gravitational instabilities and local accumulation of pyroclasts affect conditions at the active vents, through which gas-particle jets are released. In turn, the vent geometry strongly impacts the eruption characteristics. Here, we compare five high-resolution topographic data sets (<4 cm/pixel) of volcanic craters and vents from Stromboli volcano, Italy, that were acquired by unoccupied aerial vehicle (UAV) during five field campaigns between May 2019 and January 2020. This period includes two paroxysmal explosions (3 July and 28 August 2019) and exhibited significant changes on day-to-month timescales. Our results highlight changes to vent geometry and their strong control on the directionality of explosions. Recurrent UAV surveys enable the monitoring of temporal morphologic changes and aid the interpretation of observed changes in eruption style. Ultimately, this may contribute to repeatedly revised risk areas on permanently active volcanoes, especially those that are important tourist destinations.